Massive hemoperitoneum without peritoneal signs: An unusual presentation of omental ectopic rupture. A case report - Emily Van Antwerp; Samuel Schick; Hunter Cutlip; Jason Turner; Jessica Hott (Elsevier, 2021)
Background: Extrauterine ectopic pregnancy is a rare form of ectopic pregnancy, accounting for roughly 1:10,000-30,000 of all pregnancies. Primary omental pregnancy is the least common form of abdominal ectopic pregnancies, making it extremely rare. Typical presentation includes pelvic pain, secondary amenorrhea, with or without vaginal bleeding. Atypical presentations range from nonspecific pain to asymptomatic. Case: A 19-year-old woman presented to the emergency department after several syncopal episodes. She had a positive urine pregnancy test (serum hCG 446 IU/L). Her hemoglobin level was 10.6 g/dL. Due to lack of pain or bleeding, abdominal imaging was not indicated. A head CT scan rendered negative results. She was subsequently diagnosed with idiopathic headaches and anemia and was discharged. She returned to hospital 48 h later with vaginal bleeding and additional syncopal episodes. She was not experiencing any abdominal pain or discomfort. Her anemia worsened (hemoglobin 7.5 g/dL). For this reason, imaging was performed. It was significant for massive hemoperitoneum. Due to the imaging findings and worsening anemia, diagnostic exploratory laparoscopy was recommended to evaluate for ruptured ectopic pregnancy. Laparoscopic findings revealed large hemoperitoneum and a 10-week gestational sac attached to the greater omentum near the transverse colon. This exceedingly rare presentation of extrauterine ectopic pregnancy offered few clinical clues other than worsening anemia until imaging later revealed the abnormality. Ruptured ectopic pregnancy, a potentially fatal complication of pregnancy, should be included into the differential diagnosis of any gravid patient with syncope and anemia unexplained by extensive diagnostic workup.